First clinical study of a novel complete metal-free ceramic total knee replacement system. Issue 1 (December 2016) - Meier, E.; Gelse, K.; Trieb, K.; Pachowsky, M.; Hennig, F.; Mauerer, A.
Abstract Background The aim of the study was to evaluate the safety and efficacy of a novel metal-free ceramic total knee replacement system. Methods Thirty-eight primary total knee arthroplasties (TKAs) were performed on 34 patients using the metal-free BPK-S ceramic total knee replacement system with both the femoral and tibial components of an alumina/zirconia ceramic composite. The clinical outcome was evaluated pre- and postoperatively at 3 (n  = 32 TKA) and 12 months (n  = 32 TKA) using the Knee Society Score (KSS), the Oxford Knee Score and the EQ-5D. Safety analysis was performed by radiological examination and assessment of adverse events. Results Postoperatively, the KSS, Oxford Knee Score and EQ-5D improved significantly at 3 and 12 months (p  < 0.001). Non-progressive partial radiolucent lines were observed in six cases, but there was no osteolysis and no implant loosening. Induction or exacerbation of allergies did not occur during the follow-up. Conclusions The metal-free BPK-S ceramic total knee replacement system proved to be a safe and clinically efficient alternative to metal implants in this short-term follow-up study.